PENGARUH JENIS MULSA DAN KONSENTRASI PUPUK ORGANIK CAIR SUPER BIONIK TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) - Ainun Marliah; Nurhayati Nurhayati; Tarmizi Tarmizi (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2012)
The study was aimed at determining effect of mulch type and concentration of liquid organic fertilizer Super Bionic on growth and yield of onion. The experiment used a randomized complete block design (RCBD) 3x3 with 3 replications. There were 2 factors investigated, 1) type of mulch consisting of 3 levels: straw, burned husk, and water hyacinth and 2) concentration of organic liquid fertilizer Super Bionic consisting of 3 levels: 2 cc/L of water, 4 cc/L of water and 6 cc/L of water. The results showed that the type of mulch significantly affected the number of tubers per hill, but did not exert significant effects on plant height and number of tillers at ages 15, 30 and 45 days after planting (DAP), wet weight of tuber per hill and dry weight of tubers per hill and potential yield. Growth and yield of onion tended to be better at water hyacinth mulch. Concentration of liquid organic fertilizer Super Bionic significantly affected the number of tillers at age 15, 30 and 45 DAP and dry weight of tuber per hill, but did not exert significant effects on plant height at age 15, 30 and 45 DAP, the number of tubers per hill, wet weight of tuber per hill and potential yield. Better growth and yield were obtained at concentrations 2 cc/L of water. There was no significant interaction between type of mulch and concentration of liquid organic fertilizer Super Bionic.